Microwave synthesis, crystal structure, antioxidant, and antimicrobial study of new 6-heptyl-5,6-dihydrobenzo[4,5]imidazo[1,2-c]quinazoline compound - Hasan H.A.; Abdulmalek E.; Rahman M.B.A.; Shaari K.B.; Yamin B.M.; Chan K.W. (BioMed Central Ltd., 2024)
Indexed by WOS/SCOPUS/ERA